2022
DOI: 10.3389/fpsyg.2022.1043921
|View full text |Cite
|
Sign up to set email alerts
|

Social isolation and loneliness among Chinese older adults: Examining aging attitudes as mediators and moderators

Abstract: Due to labor migration and social changes, the Chinese elderly are facing significant social isolation, along with changes in aging attitudes. However, whether social isolation affects loneliness among the Chinese elderly and whether this relationship is moderated and mediated by aging attitudes is unclear. This empirical study aimed to respond to the above questions in the Chinese context, Based on the data from the 2014 China Longitudinal Aging Social Survey (N = 6,645), the results showed that social isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…25,26 Research indicates that approximately one-third of Chinese older adults reported social isolation or loneliness. 25,27 As effective treatments for dementia are currently unavailable, various interventions, both in-person and online, are accessible to combat social isolation and loneliness. Therefore, investigating the relationship between social isolation, loneliness, and MCR may enable the development of effective preventive and mitigative strategies for predementia and dementia in China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 Research indicates that approximately one-third of Chinese older adults reported social isolation or loneliness. 25,27 As effective treatments for dementia are currently unavailable, various interventions, both in-person and online, are accessible to combat social isolation and loneliness. Therefore, investigating the relationship between social isolation, loneliness, and MCR may enable the development of effective preventive and mitigative strategies for predementia and dementia in China.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, social isolation and loneliness have become increasingly prevalent among Chinese older adults due to rapid aging, decreased fertility rates, and urbanization 25,26 . Research indicates that approximately one‐third of Chinese older adults reported social isolation or loneliness 25,27 . As effective treatments for dementia are currently unavailable, various interventions, both in‐person and online, are accessible to combat social isolation and loneliness.…”
Section: Introductionmentioning
confidence: 99%
“…The disparities observed in the findings between our study and Qi’s study may also be attributed to the differential influence of social context on the experience of loneliness ( Rokach et al, 2001 ). Chinese culture, with its extensive family networks and adherence to traditional Confucian-based filial piety ( Sun et al, 2022 ), likely contributes to mitigating feelings of loneliness and poor oral health outcomes among older adults. In contrast, Japanese culture is characterized by a perception of social rigidity, which pertains to the perceived challenges of voluntarily joining or leaving social groups and establishing new social connections ( Badman et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Third, the proportion of PCI and their caregivers experiencing loneliness in this study was relatively lower than that reported in Western contexts [ 43 ]. Although levels of loneliness among older adults tend to be lower in Asian societies [ 44 , 45 ], future studies may revisit the validity of the instrument measuring loneliness in local languages. Fourth, the generalizability of our findings is constrained by its focus on a single community in a developed, small city-state before the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%